Factors Affecting Corporate Taxpayer Compliance in Central Maluku Regency - Nurhani Latuconsina; Jefry Gasperz; Ferry H. Basuki (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study aims to analyze the effect of E-Invoice, E-Filling, E-Billing and E-SPT on taxpayer compliance. This study used quantitative research methods with Partial Least Square (PLS) analysis tools samples used by 35 respondents. The results showed that the E-Invoice system has a positive and significant influence on taxpayer compliance. E-Filling also has a positive and significant influence on taxpayer compliance. Furthermore, E-Billing has a positive and significant influence on taxpayer compliance. And E-SPT has a positive and significant influence on taxpayer compliance